Prevzem kot korporacijsko dejanje na evropski poravnalni platformi T2S - Titan, Matjaž (Podjetje in delo, 2015)
In February 2017, KDD (Slovenian CSD) shall migrate to T2S System (Target2-Securities), which is a common European platform established in order to perform the settlement of securities. Since a common system requires a high level of harmonized rules regarding its operations, it is mandatory for KDD to preliminarily adjust its settlement process with CASG/CAJWG corporate actions standards in use by T2S System. One of such corporate actions being takeover, the following will be the most significant changes applied to takeover bid procedure as laid down in Takeovers Act (ZPre-1): modification of manner to pay the purchase price to acceptor, restricting the role of KDD member acting on behalf of the bidder, and redefining the moment when the contract between the bidder and acceptor is deemed concluded. All the changes mentioned have already been observed upon the preparation of the draft Act amending the Takeovers Act (ZPre-1G).
Keywords: korporacije; podjetja; prevzem; vrednostnih papirji